Primary Retroperitoneal Mucinous Cystadenoma with a Sarcoma-Like Mural Nodule: Ultrasound and MRI Findings - Poyraz, Ahmet Kürşad; Akyol, Muammer; Kocakoç, Ercan (Fırat University, 2013)
Primary retroperitoneal mucinous cystadenoma with a sarcoma-like mural nodule is a rare entity with one case reported in literature. We present a case of a 34-year-old woman who presented for evaluation of gastric pain, where a cystic abdominal mass was incidentally seen on ultrasonography. Subsequent magnetic resonance imaging (MRI) showed signal characteristics of a retroperitoneal cystic mass with hemorrhagic content and a mural nodule. After one year there was no evidence of recurrence or metastasis on follow-up ultrasonography.

Sarkom benzeri mural nodülü bulunan primer retroperitoneal müsinöz kistadenom daha once literatürde bir defa bildirilmiş nadir bir kitledir. Mide ağrısının değerlendirilmesi amacıyla başvuran 34 yaşındaki kadın hastanın ultrasonografisinde insidental olarak görülen kistik karın kitlesini sunuyoruz. Takip eden manyetik rezonans görüntüleme (MRG) retroperitoneal kistik kitlenin hemorajik içeriği ve mural nodülünün sinyal karakteristiğini ortaya koydu. Birinci yılsonunda takip ultrasonografide nüks ya da metastaz bulgusu izlenmedi.
Sarkom Benzeri Mural Nodülü Bulunan Primer Retroperitoneal Müsinöz Kistadenom: Ultrason ve MRG Bulguları